Eu sou, eu era, não sou mais : relatos de sujeitos fal(t)antes em suas vidas entre línguas - Megale, Antonieta Heyden (2012)
There are over 200 languages spoken in Brazil. Moreover, one cannot ignore the impact of globalization. As McGrew and Held (1992) argue, it connects communities in new combinations of time-space, making the world more interconnected. Another triggering factor of the interest in foreign languages in Brazil was the economic rise of low income classes, which represent more than 90 million Brazilians with access to education and the labor market. Thus, the search for language schools has increased considerably, as well as the number of Brazilians who have the possibility to study abroad or who opt for bilingual or international schools. Faced with this data, the objective of this research is to study the functioning of language in the constitution of the subjectivity of individuals, pointing to identity shifts in the discourse of speakers of English and Portuguese. The corpus was gathered from questionnaires answered by simultaneous and sequential bilingual individuals. As to the analysis of the corpus a transdiciplinary approach is adopted. It includes concepts from French discourse analysis with theoretical contributions from psychoanalysis, as well as authors who study identity such as Hall (2005), Norton (1995), Bauman (2005) and Ciampa (1984, 1990, 2004). Thus, identity is here understood (i) as having its existence in the imagination of the subject which according to Coracini (2007) is built through and by overlapped discourses which constitute the subject; the discourse of science, of the colonized and of the media and (ii ) as a process of metamorphosis from an identity that is always assumed (Ciampa, 1984). The analysis of data suggests that there are different ways of living between languages, but it is impossible to deny that speaking more than one language prints, as Coracini (2007) states, indelible marks on the subjects identities which are (re) built all the time